EFL Students’ Perceptions of Quillbot as a Paraphrasing Tool to Prevent Plagiarism in Academic Writing - Hindriana, Aprilia Devi; Hapsari, Christianti Tri (IKIP Siliwangi, 2026)
Students required to produce plagiarism-free work when writing for academic purposes; therefore this study aims to explore students’ perceptions of QuillBot as a paraphrasing tool to prevent plagiarism and the challenges they face when utilizing it in academic writing. Thirty seventh-semester English Language Education Study Program students from Universitas Negeri Semarang participated in this qualitative study. Data were collected through questionnaires distributed to all participants and interviews with six participants who were purposefully chosen based on their questionnaire responses. The findings reveal that students have a positive perception toward using QuillBot in academic writing. QuillBot is considered capable of reducing text similarity to the original source, speeding up the paraphrasing process, increasing productivity, simplifying complex sentences, and boosting student’s confidence in producing plagiarism-free work. This study also identified several challenges that students encountered when using QuillBot, including limitations with free accounts and paraphrased results that were sometimes out of context. This study implies that integrating guided instruction on the effective use of QuillBot can help students develop academic writing skills; however, further research is needed to gain a better understanding of the impact of using the QuillBot paraphrasing tool on student academic writing development.